Pengaruh Variasi Lama Maserasi Pelarut Air Terhadap Aktivitas Antioksidan dan Antibakteri Propolis Lebah Madu Trigona sp. - Amaliah, Fadhilah Rizqi; Handayani, Baiq Rien; amaro, moegiratul; Werdiningsih, Wiharyani (Pro Food, 2025)
Propolis is a resinous product collected by honeybees from plant sources, used as a colony protectant and barrier against pathogenic microorganisms. Propolis is rich in bioactive components with potential antioxidant and antibacterial properties. This study aimed to evaluate the effect of varying maceration times using water as a solvent on the antioxidant and antibacterial activities of Trigona sp. honey bee propolis. The study used a completely randomized design with a single factor: maceration time (6, 12, 18, and 24 hours) and 5 replicates. Measured parameters included antioxidant activity, phytochemical screening, pH, and bacterial inhibition zone of Eschericia coli. Data were analyzed using ANOVA (Analysis of Variance), followed by the Honestly Significant Difference (HSD) test if significant differences were found (α=0.05). Descriptive analysis was used for phytochemical screening data. The results showed that maceration time had a significant effect on the antioxidant activity, pH, and inhibition zone of Trigona sp. propolis. Extracts with different maceration times resulted in liquid propolis that tested positive for alkaloids, flavonoids, phenolics, tannins, and saponins. The liquid propolis produced from 6-hour maceration had the highest antioxidant activity (88.82%), while 24-hour maceration produced the widest inhibition zone (2.95 mm).